2016
DOI: 10.1183/13993003.00066-2016
|View full text |Cite
|
Sign up to set email alerts
|

The economic effects of supporting tuberculosis-affected households in Peru

Abstract: The End TB Strategy mandates that no tuberculosis (TB)-affected households face catastrophic costs due to TB. However, evidence is limited to evaluate socioeconomic support to achieve this change in policy and practice. The objective of the present study was to investigate the economic effects of a TB-specific socioeconomic intervention.The setting was 32 shantytown communities in Peru. The participants were from households of consecutive TB patients throughout TB treatment administered by the national TB prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
81
2
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(89 citation statements)
references
References 19 publications
1
81
2
5
Order By: Relevance
“…Firstly, we were unable to account for changes in mobile phone access over the course of each patient's illness. A high proportion of patients with TB in Peru incur TB‐related catastrophic costs and report dissaving behaviours to cope with the financial burden associated with their disease . This may mean that when challenged by TB‐associated direct and indirect costs they must sell their phone, give up their network subscription or not have enough phone credit to communicate during the time that they are unwell.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we were unable to account for changes in mobile phone access over the course of each patient's illness. A high proportion of patients with TB in Peru incur TB‐related catastrophic costs and report dissaving behaviours to cope with the financial burden associated with their disease . This may mean that when challenged by TB‐associated direct and indirect costs they must sell their phone, give up their network subscription or not have enough phone credit to communicate during the time that they are unwell.…”
Section: Discussionmentioning
confidence: 99%
“…A study in India showed that patients who received monthly food rations had a 50% lower risk of unsuccessful treatment outcomes than those who received no food support . Another study showed that patients who receive socio‐economic support are more likely to complete treatment and be ‘cured’ and less likely to incur catastrophic costs . Thus, in our study transportation reimbursement and nutritional support could be important factors contributing to improved outcomes during the CHW intervention.…”
Section: Discussionmentioning
confidence: 60%
“…Infection of patients ends practically in 2-3 weeks with effective treatment. (1,2) According to the report of the World Health Organization: 10.4 million people were infected with tuberculosis in 2016 and 1.7 million people died due to tuberculosis. (2) As in developing countries, TB still remains a major problem in our country.…”
Section: Introductionmentioning
confidence: 99%
“…(1,2) According to the report of the World Health Organization: 10.4 million people were infected with tuberculosis in 2016 and 1.7 million people died due to tuberculosis. (2) As in developing countries, TB still remains a major problem in our country. In particular, the insufficiency of TB diagnosis, treatment and follow-up has begun to pose a significant threat to public health.…”
Section: Introductionmentioning
confidence: 99%